Panic disorder - Rachman, Stanley (Oxford University Press, 2004)
This new edition of Panic Disorder: The Facts includes valuable new information on treatment and discusses the relationship between panic disorder and other anxiety conditions. It also assesses the evidence for the available treatments, drawing from the latest scientific research. Information on self-help has also been revised. Up-to-date information on the nature, symptoms, causes, theories and treatment of panic disorder is provided, an in non-technical language. The chapters on treatment give a detailed account of psychological therapy and also discuss drug treatment. A final chapter answers some commonly asked questions. Numerous personal accounts are given throughout the book, highlighting various aspects of panic disorder and its treatment